2004
DOI: 10.1002/macp.200300098
|View full text |Cite
|
Sign up to set email alerts
|

Atom Transfer Radical Polymerization Using Multidentate Amine Ligands Supported on Soluble Hyperbranched Polyglycidol

Abstract: Summary: Controlled polymerization of styrene in toluene was achieved by atom transfer radical polymerization (ATRP) using hyperbranched polyglycidol‐supported multidentate amine ligands/CuIBr catalyst systems. These catalyst systems with nanoscopic dimensions were more active than the corresponding low‐molecular‐weight ligands. The controlled/living nature of the polymerization is supported by linear first order plots (ln[M]o/[M] versus time) and a linear increase of $\overline M _{\rm n}$ versus conversion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 29 publications
(40 reference statements)
0
29
0
Order By: Relevance
“…Different methods were taken into account to stabilize nanometals on the support using various types of functional molecules such as polymers, surfactants, and different types of ligands as capping agents. Both dendrimers and hyperbranched polymers covalently or noncovalently functionalized with catalytically active transition metal complexes are one of promising scaffolds with respect to catalyst recovery . In many aspects, dendrimers can be replaced by hyperbranched polymers due to their similar properties, such as low viscosity, high functionalities and spheroid‐like shape.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different methods were taken into account to stabilize nanometals on the support using various types of functional molecules such as polymers, surfactants, and different types of ligands as capping agents. Both dendrimers and hyperbranched polymers covalently or noncovalently functionalized with catalytically active transition metal complexes are one of promising scaffolds with respect to catalyst recovery . In many aspects, dendrimers can be replaced by hyperbranched polymers due to their similar properties, such as low viscosity, high functionalities and spheroid‐like shape.…”
Section: Introductionmentioning
confidence: 99%
“…Both dendrimers and hyperbranched polymers covalently or noncovalently functionalized with catalytically active transition metal complexes are one of promising scaffolds with respect to catalyst recovery. [21][22][23] In many aspects, dendrimers can be replaced by hyperbranched polymers due to their similar properties, [24] such as low viscosity, high functionalities and spheroid-like shape. The silica-supported palladium nanoparticles-mediated organic transformations have been developed remarkably.…”
Section: Introductionmentioning
confidence: 99%
“…Selier M et al reported that Boltorn type HPPs can be used as distillation extractant and possess better function than linear polyhydric alcohol, such as 1,6-hexanediol [6,7,8]. Siriba et al and Kumar et al reported respectively that HPPs can be used as catalyst delivery via formation of covalent bonds of the terminal hydroxyls and catalyst [9,10]. On the other hand, HPPs can be easily modified through the conversion of end groups; Kishore K. Jena et al reported that a series of organic-inorganic hybrid coatings from hyperbranched polyurethanes were prepared using HPEP and 3-aminopropyltriethoxysilane [11].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular weights, intrinsic viscosity [Z], hydrodynamic radii (R h ), and radii of gyration (R g ), were determined by gel permeation chromatography (GPC) with a triple detector; the details have been described earlier. [7] The dn/dc value for polyglycidol was determined to be 0.12 cm 3 Á g À1 . Hydrodynamic radii (R h ) of esterified polymers were measured at room temperature (22 8C) using a DAWN EOS multi-angle laser light scattering (MALLS) instrument from Wyatt Technology Corp. equipped with a Wyatt Quasi Elastic Light Scattering (QELS) correlator.…”
Section: Introductionmentioning
confidence: 99%